ANALISIS KESALAHAN PESERTA DIDIK BERDASARKAN NEWMAN’S ERROR ANALYSIS DALAM PENYELESAIAN SOAL MATEMATIKA KELAS VIII DI SMP NEGERI 13 PADANG - Krisdayanti, Novi (Jurnal Edukasi dan Penelitian Matematika, 2024)
Achievement of mathematics learning can be seen through by evaluation. Based on the evaluation results in class VIII SMPN 13 Padang is still low, the students have difficulty in solving mathematics problems. Therefore, an analysis of these errors is carried out to measure the quality of students' answers using error analysis based on Newman's Error Analysis (NEA). The type of research is qualitative research with a descriptive approach, the research subjects are six class VIII students at SMPN 13 Padang. Data collection techniques are written tests and interviews. The results of the study showed that the types of errors made by students of class VIII SMPN 13 Padang in solving the Pythagoras theorem based on Newman's error analysis consisted of (a) reading and comprehension errors of 32.53%; (b) transformation errors of 28.01%; (c) process skills errors of 15.36%; (d) encoding errors of 24.10%. The types of errors made by high group students in general are encoding errors. The types of errors made by medium group students in general are, transformation, process skills and encoding errors. The types of errors made by low group students are, reading and comprehension, transformation, process skills, and encoding errors.Keywords– Error Analysis, Newman's Error Analysis, Pythagoras Theorem